2022
DOI: 10.1038/s41467-022-31217-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional but not obligatory link between microsaccades and neural modulation by covert spatial attention

Abstract: Covert spatial attention is associated with spatial modulation of neural activity as well as with directional biases in fixational eye movements known as microsaccades. We studied how these two ‘fingerprints’ of attention are interrelated in humans. We investigated spatial modulation of 8-12 Hz EEG alpha activity and microsaccades when attention is directed internally within the spatial layout of visual working memory. Consistent with a common origin, spatial modulations of alpha activity and microsaccades co-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
186
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(217 citation statements)
references
References 53 publications
(77 reference statements)
29
186
2
Order By: Relevance
“…Whatever the exact physiological origins of the here-reported microsaccade-locked transient alpha lateralisation, our results – together with those before us 10,1417,33,4951 – carry a relevant practical implication. They highlight the importance of considering microsaccades when reporting neural modulation by specific task variables.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Whatever the exact physiological origins of the here-reported microsaccade-locked transient alpha lateralisation, our results – together with those before us 10,1417,33,4951 – carry a relevant practical implication. They highlight the importance of considering microsaccades when reporting neural modulation by specific task variables.…”
Section: Discussionsupporting
confidence: 69%
“…Like here, we found that alpha lateralisation and microsaccade direction correlated – when microsaccades occurred. However, we also found that microsaccades were not necessary, since task-driven alpha lateralisation was preserved in trials without microsaccades 10 (see also 52 ). The present report suggests that explorations of this type should be adopted more widely.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…First, although attention-related modulations of cortical and subcortical processing are larger during trials containing microsaccades towards the location of a (covertly) attended stimulus, clear attention-related modulations are also observed in the absence of microsaccades (Yu et al, 2022;Liu et al, 2022; though see Lowet et al 2018 for a contradictory result). Second, any of the three models examined in the current study (i.e., retro-capture, automatic refreshing, or delayed selection) could have produced the delays in microsaccade biases reported by van Ede et al ( 2020).…”
Section: Discussionmentioning
confidence: 99%